Involvement of long non-coding RNA (lncRNA) MALAT1 in shear stress regulated adipocyte differentiation - Caron, Justin; Ghanbariabdolmaleki, Marjan; Marino, Madison; Qiu, Chong; Wang, Bo; Mak, Michael; Wang, Shue (Frontiers in Bioengineering and Biotechnology, 2025)
Adipocyte differentiation plays an important role in bone remodeling due to secretory factors that can directly modulate osteoblast and osteoclast, thus affecting overall bone mass and skeletal integrity. Excessive adipocyte differentiation within the bone marrow microenvironment can lead to decreased bone mass, eventually causing osteoporosis. The mechanical microenvironment of bone marrow, including fluid shear, maintains the balance of adipocyte and osteoblast differentiation during bone remodeling. However, how mechanical cues interact with long noncoding RNA (lncRNA) and regulate adipocyte differentiation remains unexplored. In this study, we investigated the mechanosensitive role of lncRNA MALAT1 during mesenchymal stem cells (MSCs) adipocyte differentiation. By applying physiologically relevant shear stress, MSCs experienced morphological changes and adipocyte differentiation differences. Shear stress inhibits adipocyte differentiation of MSCs, demonstrated by reduced oil-red-o-stained lipid droplets. Silencing MALAT1 also results in reduced adipocyte differentiation. By leveraging a novel gapmer double stranded locked nuclei acid nanobiosensor, we showed that shear stress inhibits MALAT1 expression, with significantly reduced fluorescence intensity. Our findings indicate that shear stress influences adipocyte differentiation mainly through the downregulation of MALAT1, highlighting a significant interplay between biophysical cues and lncRNAs. This interaction is crucial for understanding the complexities of bone remodeling and the potential therapeutic targeting of lncRNAs to treat bone-related disorders.